Lectura(s) desde la literatura fantástica de Cara a Times Square de Camilo Gonsar - Juárez Morena, Pablo (Madrygal. Revista de Estudios Gallegos, 2005)
The document starts with a brief theoretical introduction to the concept of fantastic literature and its impact in Galician literature. Then, it focuses on the study of Camilo Gonsar’ novel Cara a Times Square, digging into the various crítical readings offered by the novel from the perspective of the fantastic literature in Galician.
Keywords: Fantastic literature; Galician literature; critical reading; literary criticism